PENGETAHUAN SIKAP DAN TINDAKAN PENDERITA TB PARU DALAM MENCEGAH KONTAK SERUMAH DI PUSKESMAS BAGANSIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR PROVINSI RIAU - Sri Endah Riestina; Suyanto "; Rohani Lasmaria Simbolon (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTTuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which most commonly affect the lungs. It’s transmitted, from person to person through (droplets nuclei). Indonesia is the fourth country with the highest TB cases in the world. In Indonesia, tuberculosis is the number one killer among infectious diseases and the third cause of death after heart disease and acute respiratory all the ages. Families who live with TB patients have a greater risk to contracting TB because it can not avoid direct contact with patients. Transmission of pulmonary TB disease can be prevented if pulmonary TB patients have the knowledge, attitude and precaution towards the prevention household contacts. The purpose of this study is to determine the knowledge attitudes and practises in preventing pulmonary tuberculosis patients at health centers household contacts in Puskesmas Bagansiapiapi Kecamatan Bangko Kabupaten Rokan Hilir Provinsi Riau. This is a descriptive observational study with cross sectional approach. The study was held in February 2015. The instrument used was a questionnaire of knowledge, attitudes, and precaution. Respondents in this study were as many as 67 people who are pulmonary TB patients were registered on the form TB 06 (BTA +) in Puskesmas Bagansiapiapi Kecamatan Bangko Kabupaten Rokan Hilir Provinsi Riau has met the inclusion criteria. The results of this study showed that the respondents have a good level of knowledge about tuberculosis as many as 36 people (53.8%) and followed by lack of 31 people (46.2%), good attitude as many as 34 people (50.7%) and followed by a total of 33 persons (49.3%), good precaution as many as 48 people (71.7%), followed by lack many as 19 people (28.3%).Key words: Tuberculosis, knowledge attitudes and precaution, patients pulmonary tuberculosis, hearts prevent contact at home